Sosialisasi Pentingnya Kesadaran Penggunaan Antibiotik Serta Bahaya Resistensi Antibiotik di SMAN 18 Jakarta - Widya Handayani; Syahrul Munir; I Putu Aris Septa Permana; Eka Saputri; Nanda Rahma Desra; Sagita Feronica Sagita (Khidmah Nusantara, 2026)
Antibiotic resistance is a growing global health problem caused by the irrational use of antibiotics in humans, animals, and the environment. The high prevalence of infectious diseases, low public awareness, and inappropriate antibiotic use practices contribute to the emergence of resistant microorganisms, which can reduce treatment effectiveness and increase morbidity and mortality rates. This community service activity aimed to improve students’ knowledge and awareness of the importance of rational antibiotic use and the dangers of antibiotic resistance. The activity employed an educational counseling method and was conducted among 11th-grade students at SMAN 18 Jakarta using a pre-test and post-test design. A total of 60 students participated in the educational session delivered through presentations and interactive discussions. The evaluation instrument consisted of 10 multiple-choice questions to assess knowledge levels before and after the intervention.The results showed a significant increase in knowledge, with the average score rising from 71% in the pre-test to 88% in the post-test. This improvement indicates that the educational intervention was effective in enhancing students’ understanding of antibiotic resistance and the prevention of antibiotic misuse. This educational activity is expected to contribute to reducing antibiotic resistance in the community.